AVIFAUNE DE LA VILLE DE YAMOUSSOUKRO, CENTRE DE LA COTE D’IVOIRE - Michaël, Konan Ekoun; Hilaire, Yaokokore-Beibro K.; Guillaume, Odoukpe Kadjo Saint; Sonia, Kouadja Kra Ehouabolet (European Scientific Journal, ESJ, 2014)
During two years, the first general ornithological survey of the city of Yamoussoukro, the political capital city, in the center of Côte d’Ivoire was conducted using point count method. Only qualitative data were considered and species were recorded on the presence-absence counts. This method allowed counting of 188 species of birds divided into 18 orders and 43 families. The study site has 105 open habitat species dwellers, 51 waterfowl species, 126 resident species, and 24 typically migratory species. Thirtyeight species of mixed origin were also recorded. The environment serves also as habitat of 17 Guineo-Congolian forest endemic species forests and eight Sudano-Guinean savanna endemic species. These important figures show a real interest for birds in this urban environment that is ultimately not a wasteland.